Outcomes of open neck injuries - Dongsub Noh; Jin Ho Choi (Journal of Trauma and Injury)
Purpose The neck is a particularly critical region for penetrating injuries due to the close proximity of the trachea, esophagus, blood vessels, and the spinal cord. An open neck injury has the potential for serious morbidity and mortality. The purpose of this study is to evaluate the assessment and management of open neck injuries. Methods In this retrospective study, open neck injury patients who were admitted to the Trauma Center of Daejeon Eulji Medical Center, Eulji University between December 2015 and December 2017 were analyzed for epidemiology, the mechanism of trauma, the injured organ, complications, and mortality. Results Thirty-two patients presented with open neck injuries. All patients underwent computed tomographic angiography to evaluate their injuries once their vital signs stabilized. Among these patients, 27 required surgical treatment. The most commonly injured organ was the airway. There were five deaths, and the main cause of death was bleeding. Mortality was associated with the initial systolic blood pressure at the hospital and Glasgow Coma Scale. Conclusions Mortality from open neck injuries was associated with initial systolic blood pressure at the hospital and Glasgow Coma Scale.